Prevalence and risk factors of antituberculosis drug-induced hepatisis in Hospital Universiti Sains Malaysia - Omar, Ahmad Marzuki (2006)
Background Tuberculosis is one of the major diseases worldwide, affecting about one-third of the world's population. The introduction of antituberculosis drugs decades ago has improved tremendously the outcome of those infected with tuberculosis. Among the drugs, isoniazid, rifampicin and pyrazinamide had been proven to be effective, but not without the side effects, of which hepatotoxicity is the most important. Antituberculosis drug-induced hepatitis has been reported and many risk factors had been recognized. Objectives This case control and observational study was conducted to determine the prevalence of antituberculosis drug-induced hepatitis in Hospital Universiti Sains Malaysia, to determine the risk factors in relation to the development of drug-induced hepatitis as well to observe the clinical course in patients with antituberculosis druginduced hepatitis. Method This study examined the evidence of antituberculosis drug-induced hepatitis in patients treated for tuberculosis in Chest Clinic for a period of 30 months from January 2003 until June 2005. Eligible cases of drug-induced hepatitis were selected and compared with controls which were selected by Simple Random Sampling in terms of demographic data and risks involved such as age, gender, body mass index, hepatitis B carrier, HIV infection, sites of tuberculosis, and pretreatment liver biochemistries such as serum albumin, globulin, AST, AL T and bilirubin. The clinical course of patients of hepatitis was also examined in term of onset, severity and duration of hepatitis, as wellas the presence of jaundice. Data were evaluated by k.hi square and independent t test (univariate) and binary logistic regression analysis (multivariate). Results A total of 4 73 patients were registered dwing the period of the study, 46 patients were noted to have antituberculosis drug-induced hepatitis and eligible for the study. 138 patients were selected as controls. The prevalence of drug-induced hepatitis was 9.7%. Among the risk factors evaluated, the presence of HIV infection (p=0.05), extrapulmonary tuberculosis (p=0.08), lower serum albumin (p=0.023) and higher serum globulin (p=0.025) were noted to be significant at univariate analysis. On binary logistic regression analysis, the presence of HIV infection (p=O.O 18) and extrapulmonary tuberculosis (p=0.017) were noted to be significant risk factors. Observation of the clinical course of patients who had drug-induced tuberculosis, showed that most of them had mild hepatitis (58.7%) and moderate hepatitis (32.6%). The onset of hepatitis mostly occurred between one to two weeks (32.6%) and two to three weeks (17.4%). The duration of hepatitis was mostly from one week (34.8%) to two weeks (32.6% ). The occurrence of jaundice was 32.6 percent. Conclusion The prevalence of antituberculosis drug-induced hepatitis was 9. 7 percent. The presence of HIV infection and extrapulmonary tuberculosis were significant risk factors for the development of hepatitis. Most of the patients who developed antituberculosis drug-induced hepatitis had mild symptoms and signs. Patients with risk factors should be monitored closely for the development of drug-induced hepatitis.